Managers' Business & Corporate Education in the System of Sustainable Development of the Organization - Dmytro KILDEROV; Stanislav PETKO; Myroslava MALYSH; Maksym MOSKALOV; Olena KOVALCHUK (Communications of International Proceedings, 2020)
Due to the changes taking place in all spheres of public life, the emphasis in the issues of staff's education and advanced training and their professional development is transferred from the national to the institutional level. Accordingly, the issue of creating, on the one hand, an effective system of education and advanced training, and on the other - an in-house system of methodical work becomes important. The set of components of the system of scientific and methodological support of the managers' professional development has been separated. The criteria for the classification of the forms and methods of managers training were systematized and substantiated, in particular: activity of the adult student; number of participants; place of study, time and duration of the study. Forms and methods of diagnosing the needs of managers, forms and methods of training, forms and methods of evaluating learning outcomes were structured and analyzed in detail.
Keywords: Business Education; Corporate Education; Transnational Company; Vocational Training; Human Resources.